Capital aspects and share ownership towards banking financial performance in ASEAN member countries - Mohammad Nadjib Usman (STIE Perbanas Surabaya, 2019)
This research was conducted to examine the effect of capital structure and ownership structure on profitability in the banking sector in Indonesia and the Philippines in 2013-2017. It used the population from conventional commercial banks listed on the Stock Exchange in Indonesia and the Philippines. The data were analyzed using statistical analysis with a structural model. Hypothesis testing results show that the capital structure (DER, CAR, and LDR) affects the banks’ profitability in Indonesia. The ownership structure (managerial ownership and institutional ownership) has a significant positive effect on the banks’ profitability also in Indonesia. However, the capital structure (DER, CAR, and LDR) has no effect on the banks’ profitability in the Philippines. And neither has thee capital structure (DER, CAR, and LDR) no effect on the banks’ profitability both in Indonesia and in the Philippines. The ownership structure (managerial ownership and institutional ownership) has a significant positive effect on the banks’ profitability of banks both in Indonesia and in the Philippines